FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE AS AN IMPORTANT INDICATOR OF PROFESSIONALISM FOREIGN LANGUAGE TEACHER IN PRIMARY SCHOOL (Pedagogy of Higher and Secondary Education, 2022)
The article reveals some prior directions as for investigating foreign language communication competence as a particular feature of primary school teacher professional skills.